Intermittent Oral Coadministration of a Gamma Secretase Inhibitor with Dexamethasone Mitigates Intestinal Goblet Cell Hyperplasia in Rats. (February 2014) - Aguirre, Shirley A.; Liu, Ling; Hosea, Natilie A.; Scott, Wesley; May, Jeffrey R.; Burns-Naas, Leigh Ann; Randolph, Sophia; Denlinger, Robert H.; Han, Bora
Dexamethasone was given in 2 oral dosing regimens with repeat dose oral administration of the gamma secretase inhibitor (GSI), PF-03084014, in Sprague-Dawley (SD) rats in order to evaluate the effects of coadministration of dexamethasone on GSI-induced goblet cell hyperplasia (GCH) in the intestinal tract. Safety end points were evaluated in 1 week and 1 month studies. The dosing regimens tested in the 1-month studies included a 1-week pretreatment with 1.0 mg/kg dexamethasone followed by a 3-week repeat dose treatment with 100 mg/kg GSI or concurrent intermittent treatment with 1.0 mg/kg dexamethasone on weeks 1 and 3 and repeat dose treatment with 100 mg/kg GSI for 4 weeks. Pretreatment with dexamethasone for 1 week transiently mitigated the severity of intestinal GCH for up to 1 week. Intermittent coadministration of dexamethasone on weeks 1 and 3 with GSI repeat dosing for 4 weeks mitigated intestinal GCH for up to 4 weeks post treatment. Treatment-related morbidity and mortality occurred on day 7 with 150 mg/kg GSI and 5 mg/kg dexamethasone coadministration, and on days 13, 14, and 23 with 100 mg/kg GSI and 1 mg/kg dexamethasone coadministration.